Business and Society A Critical Introduction - Birch, Kean; Laurin-Lamothe, Audrey; Scott, Sonya; Wellen, Richard (London : Bloomsbury Academic, 2023)
Corporations dominate our worlds. They employ us, sell to us and influence how we think and who we vote for. All aspects of this relationship are explored, from an historical analysis of the spread of capitalism to the regulation, ethics and exclusionary implications of business in contemporary society. The book also examines how corporate power and capitalism might be resisted and outlines a range of alternatives, from the social economy through to new forms of open access or commons ownership. This second edition includes new chapters that explore how global crises such as the Covid-19 pandemic and the climate emergency have exposed tensions within and among national business systems. It also addresses the need for new ways of holding business accountable in the era of digital platforms like Facebook, Google and Amazon, which use algorithmic personalization to exert private control over the infrastructure of our societies.
1. A critical introduction to business and society Kean Birch, Audrey Laurin-Lamothe and Sonya Marie Scott 2. The emergence of capitalism in Western Europe Mark Peacock 3. The spread of capitalism Kean Birch and Caroline Shenaz Hossein 4. Markets and economic order Mark Peacock 5. Economics, capitalism and business : the orthodoxy Sonya Marie Scott and Mark Peacock 6. Political economy and critiques of capitalism : heterodox perspectives Sonya Marie Scott 7. The corporate revolution Kean Birch and John Simoulidis 8. Corporate governance Alberto Salazar 9. Corporate responsibility Kean Birch 10. Corporate power Kean Birch 11. Corporations and financialization Audrey Laurin-Lamothe and Richard Wellen 12. Corporations and market power in the 21st century John Simoulidis 13. Global economy and varieties of capitalism Kean Birch and Richard Wellen 14. Global governance Kean Birch and Richard Wellen 15. Global migration and immigrant-led business Salewa Olawoye-Mann 16. Global environmental change Kean Birch 17. Global disorders and crises Sonya Marie Scott 18. Business, regulation and policy Richard Wellen and Alberto Salazar 19. Ethics and business Mark Peacock, Richard Wellen and Kean Birch 20. Business and social exclusion Caroline Shenaz Hossein 21. Resistance and alternatives to corporate capitalism Kean Birch and John Simoulidis 22. Social and solidarity economy Caroline Shenaz Hossein 23. From sharing economy to surveillance capitalism Richard Wellen, Kean Birch, Salewa Olawoye-Mann 24. Conclusion Richard Wellen and Sonya Marie Scott
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Business ethics; Social responsibility of business; Behavioural economics; Business ethics & social responsibility; Economics